2007
DOI: 10.1111/j.1365-2702.2006.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Findings from non‐participant observational data concerning health promoting nursing practice in the acute hospital setting focusing on generalist nurses

Abstract: Nursing programmes must highlight health promotion as integral to practice and emphasis the socio-political dimensions of health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 74 publications
4
46
0
1
Order By: Relevance
“…2005, Runciman et al. 2006, Casey 2007, Irvine 2007). Essentially, authors agree that health education practice is traditionally grounded in disease‐oriented behavioural models designed to prevent, reduce or react to an individual’s risk of illness.…”
Section: Introductionmentioning
confidence: 99%
“…2005, Runciman et al. 2006, Casey 2007, Irvine 2007). Essentially, authors agree that health education practice is traditionally grounded in disease‐oriented behavioural models designed to prevent, reduce or react to an individual’s risk of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate support of managers, particularly in case of appropriate time allocation for nurses' teaching activities and ineffective coordination of educational responsibilities among disciplines is a barrier to PE. 38,48 Managerial and organizational support is an important element for the implementation of high-quality PE. 49,50 The result of a study that was conducted in Iran showed that nurses were well informed of the importance of patient education and had accepted this role in clinical settings, but no managerial support was available to them for doing this activity.…”
Section: Exploring Factors Influenc-mentioning
confidence: 99%
“…Further research has shown that the essence in practical nursing is focused on alleviating and reducing disease and not on actively strengthening the patients’ positive aspects of health (Berg, Hedelin, & Sarvimäki, 2005). Attempts to integrate health promotion in nursing practice are often limited to a health prevention approach; that is, information-giving associated with changing lifestyle-related health behavior (Casey, 2007; Irvine, 2007; Markle-Reid et al, 2006; Whitehead 2006). Research in elderly care showed that 81% of nurses ( n = 72) described health promotion in nursing as education and information to promote healthy behaviors and lifestyles (Kelley & Abraham, 2007).…”
Section: Previous Research About Health Promotion In Nursingmentioning
confidence: 99%